Pengaruh Penggunaan Multimedia Terhadap Pemahaman Konsep Pada Mata Kuliah Pengembangan Kognitif dan Kreatifitas Anak Usia Dini Di UNSRI Palemban - Hasmalena Hasmalena; Rukiyah Rukiyah; Mahyumi Rantina (LPPM Universitas Pahlawan Tuanku Tambusai, 2018)
The influence of multimedia usage on PG-PAUD student concept understanding in cognitive development and creativity course of early childhood has been done on PG-PAUD Student semester three in Palembang Sriwijaya University. The type of research used is experiment with One Shoot Case Study descriptions, with sampling technique that is purposive sampling. The sample in the pre-experiment class is 27 and the post-test class is 28. The data collection technique is written essay, interview and documentation. Result of data analysis obtained is 80,71, while result of hypothesis test based on t-test obtained t_hitung t_table or got t_count = 6,76 t_table = 4,83, hence Ho refused and Ha accepted, thus there influence multimedia usage to understanding the concept of PG-Paud students in courses of cognitive development and creativity of early childhood. With assessment indicators Redefining a concept, Classifying objects according to certain traits according to their concepts, Providing examples of concepts, Using, utilizing and selecting specific procedures. So the use of multimedia to understanding the concept of the students is very influential to improve understanding of the concept.